2021
DOI: 10.1037/hea0001099
|View full text |Cite
|
Sign up to set email alerts
|

Child adjustment to parental cancer: A latent profile analysis.

Abstract: Objective: This study aimed to identify latent classes of adjustment in children confronted with parental cancer, based on profiles of traumatic stress symptoms, health-related quality of life (HRQoL), and satisfaction with life. In addition, correlates of classes were examined. Method: Families were recruited through social media, health care providers, and cancer support centers. The sample consisted of 175 children (52% girls, aged M = 11.98, SD = 3.20, range = 6-20 years) from 92 families, including 90 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
9

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 47 publications
0
12
0
9
Order By: Relevance
“…The current study relies on data collected at the first timepoint. A previous article on this study reported on latent classes of child adjustment, based on profiles of PTSD symptoms, HRQoL, and satisfaction with life ( Egberts et al, 2021 ). Families were eligible to participate if one of the parents had a current or past cancer diagnosis and had at least one child in the age of 0–18 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study relies on data collected at the first timepoint. A previous article on this study reported on latent classes of child adjustment, based on profiles of PTSD symptoms, HRQoL, and satisfaction with life ( Egberts et al, 2021 ). Families were eligible to participate if one of the parents had a current or past cancer diagnosis and had at least one child in the age of 0–18 years.…”
Section: Methodsmentioning
confidence: 99%
“…Clinically relevant child PTSD symptoms have been reported for 21% of sons and 35% of daughters (11–23 years old) 1–5 years after their parent’s diagnosis ( Huizinga et al, 2005b ). In a previous paper on the same sample as used in the current study, four different patterns of child adjustment were identified, based on children’s health-related quality of life (HRQoL), PTSD symptoms, and satisfaction with life ( Egberts et al, 2021 ). Whereas the majority of children (75%) displayed average to high levels of functioning, 25% of children experienced high levels of posttraumatic stress and impaired HRQoL, in some cases combined with low life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Mögliche Probleme sind, dass Kinder die Angst und Verunsicherung ihrer Eltern spüren und dann versuchen, möglichst stark zu sein, und so in ihren Emotionen missverstanden werden. In einer aktuellen Studie aus den USA zeigten 25 % der Kinder krebskranker Eltern ein hohes Level an Distress sowie eine beeinträchtigte Lebensqualität [55].…”
Section: Auswirkungen Auf Minderjährige Kinder Und Die Familieunclassified
“…The adolescent, despite mentioning that performing household chores did not interfere with school activities or relationship with the peer group, considered that his school performance was affected; however, he related this fact to changes in the emotional dimension. The quality of communication between parents and children, associated with a "warm parenting", can play a protective role in adolescents' adjustment to parental cancer, promoting more effective coping and strengthening existing relationships (13) . In the case under study, Despite the changes in family dynamics caused by parental cancer, the positive relationship of closeness with the mother before the diagnosis, the existence of open communication and the ability to maintain activities allowed to preserve and strengthen the binomial's relationship.…”
Section: Mother-child Relationshipmentioning
confidence: 99%